THE MACROECONOMIC IMPLICATIONS OF THE COVID-19 ECONOMIC CRISIS: THE CASE OF SOUTH KOREA - Yoon, Yeo Hyub (Investigación Económica, 2021)
This paper examines the major impacts of COVID-19 on the Korean economy throughout 2020. Since the start of the pandemic, sectoral unevenness of growth, employment inequality, and corporate liquidity preferences have been accelerated. These patterns reflect a continuation of trends that have been developed since the 1997 Asian crisis. As the main approach in examining the economic effects of the COVID-19 crisis and the government policy implemented to cope with them, I focus on the unequal distribution of output and employment shocks across businesses, workers, and households, through which I derive the macroeconomic implications of the pandemic crisis for the Korean economy. Throughout 2020, South Korea has been witnessing income redistribution favorable to big corporations and banks and away from small businesses, non-standard workers, and low-income households. These widening disparities have important macroeconomic implications. LAS IMPLICACIONES MACROECONÓMICAS DE LA CRISIS ECONÓMICA COVID-19: EL CASO DE COREA DEL SUR RESUMEN En este trabajo se examinan los principales impactos del COVID-19 en la economía de Corea del Sur en 2020. Desde el inicio de la pandemia el crecimiento sectorial desigual, la desigualdad del empleo y las preferencias por la liquidez se han acelerado. Estos patrones reflejan la continuación de tendencias que se han desarrollado desde la crisis asiática de 1997. Al revisar los efectos de la crisis COVID-19 y la política correspondiente implementada por el gobierno, nos enfocamos principalmente en la distribución desigual del producto y de los choques al empleo entre las empresas, los trabajadores y los hogares mediante lo cual se derivan las implicaciones macroeconómicas de la pandemia para la economía de Corea. A lo largo de 2020, Corea del Sur ha estado experimentando una redistribución del ingreso favorable a las grandes corporaciones y a los bancos y en disfavor de las pequeñas empresas, los trabajadores no estándar y los hogares de bajos ingresos. Estas disparidades crecientes tienen implicaciones macroeconómicas importantes.